Status of ecophysiological studies on forest species in Malaysia - Awang, Kamis; Mohamad, Aminuddin (1985)
Ecophysiological research can provide important information for forestry practices. This paper reports on the ecophysiological works pertaining to specific problems of Malaysian forestry. They include forest seed storage and germination, planning stock production, fertiliser requirements of plantation species, regeneration of the hill forest and productivity of rainforest species. The paper also identifies other areas that require greater research attention.